A SYSTEMATIC REVIEW OF THE USE OF TULATHROMYCIN IN VETERINARY MEDICINE - Carmen (Pop) Moldovan; Alexandra Dreancă; Oana Rotar; Mihai Madru; Ioan Marcus (Agricultura)
The study's findings can help animal health professionals explore alternative treatments for respiratory diseases in sheep and improve their overall health. The review aims to synthesize current research on the use of tulathromycin in veterinary medicine. Key studies demonstrate that tulathromycin is effective in treating bacterial pathogens responsible for respiratory disease, including Mannheimia haemolytica and Pasteurella multocida. The pharmacokinetic properties of tulathromycin, characterized by rapid absorption, extensive tissue distribution, and prolonged elimination half-life, contribute to its therapeutic advantages. Additionally, the review examines the dosage regimens, administration routes, and potential side effects reported in clinical trials. Data regarding antimicrobial resistance to tulathromycin is discrepant due to several sources that display negative results regarding the sole use of this macrolide and its off-label use. Although limitations exist, a consolidated further research on the application of tulathromycin in sheep, highlighting its benefits and addressing potential challenges in its use is needed.